Penerapan Metode Promethee Pada Aplikasi Penerima Kartu Keluarga Sejahtera (KKS) - Azizah Azizah; Khairudin Nasution (Bulletin of Informatics and Data Science, 2022)
The Prosperous Family Card or commonly referred to as KKS is a government program in poverty alleviation. This program is a development of the previous program called the Social Protection/Prosperity Card (KPS) which was implemented during the era of President Susilo Bambang Yudhoyono's administration. And therefore, to minimize the occurrence of errors in the selection of the community in getting the Prosperous Family Card (KKS), an application is needed that aims to simplify any related data processes. The method used is the Promethee method (Preference Ranking Oranization Method For Enrichment Evaluation). Promethee is a sequencing method for multi-criteria analysis. The criteria used are occupation, income, number of dependents, condition of the house and assets owned